#
4 definitions
by
**hotgirl69xxx**

Top Definition

An expression such as

x^3 + 2x^2 - 6x - 2, is a cubic expression.

3x - 4 is linear

x^2 + 5x - 10 is quadratic

These types of expressions can be extended to include higher powers of x, such as

x^5 + 3x^3 - 2x^2 + 3

4x^6 + 2x^4 - x^3 + 5

Expressions of this type are called polynomials.

Note: Polynomials do not have negative or fractional powers. n is a non-negative integer.

The degree of a polynomial is given by the highest power of the variable

x^3 + 2x^2 - 6x - 2, is a cubic expression.

3x - 4 is linear

x^2 + 5x - 10 is quadratic

These types of expressions can be extended to include higher powers of x, such as

x^5 + 3x^3 - 2x^2 + 3

4x^6 + 2x^4 - x^3 + 5

Expressions of this type are called polynomials.

Note: Polynomials do not have negative or fractional powers. n is a non-negative integer.

The degree of a polynomial is given by the highest power of the variable

An expression of the form

ax^n + bx^(n-1) + ... + px^2 + qx + r

(where a, b, ..., p, q, r are constants is called a polynomial in x)

3x^5 + 3x^4 - 2x^2 -1 is a polynomial of degree 5.

A constant expression is a polynomial of degree 0

A linear expression is a polynomial of degree 1

a quadratic expression is a polynomial of degree 2

a cubic expression is a polynomial of degree 3

etc.

ax^n + bx^(n-1) + ... + px^2 + qx + r

(where a, b, ..., p, q, r are constants is called a polynomial in x)

3x^5 + 3x^4 - 2x^2 -1 is a polynomial of degree 5.

A constant expression is a polynomial of degree 0

A linear expression is a polynomial of degree 1

a quadratic expression is a polynomial of degree 2

a cubic expression is a polynomial of degree 3

etc.

by hotgirl69xxx
December 27, 2004

2

In mathematics, we often arrive at answers that contain root signs (they may be square roots, cube roots, etc.).

We will find that some of these numbers with a root sign are easy to deal with since they have an exact decimal representation

For instance sqrt16 = 4, rt^3(8)= = 2, sqrt11.56 = 3.4, rt^5(1/32) = 0.5.

This is because each of these numbers is rational

We will find that some of these numbers with a root sign are easy to deal with since they have an exact decimal representation

For instance sqrt16 = 4, rt^3(8)= = 2, sqrt11.56 = 3.4, rt^5(1/32) = 0.5.

This is because each of these numbers is rational

Expressions with root signs involving pirrational numbers] such as sqrt7 - 2 or rt^3(5) are called surds.

by hotgirl69xxx
December 28, 2004

3

The plural of index is indices

Index is simply another word for power.

Index is simply another word for power.

a * a * a * a can be written as a^4 (a to the power of 4)

by hotgirl69xxx
December 28, 2004

4

the reverse process of differentiaton

we know that, for example if f(x) = 2x^3 - 5x^2 + 3x -7

then f'(x) = 6x^2 - 10x + 3

This process can be reversed.

In general, y = x^n -> dy/dx = nx^(n-1)

So, reversing this process, it would seem that dy/dx = x^m -> y = (1/(m+1))x^(m+1)

The general process of finding a function from its derivative is known as interation.

we know that, for example if f(x) = 2x^3 - 5x^2 + 3x -7

then f'(x) = 6x^2 - 10x + 3

This process can be reversed.

In general, y = x^n -> dy/dx = nx^(n-1)

So, reversing this process, it would seem that dy/dx = x^m -> y = (1/(m+1))x^(m+1)

The general process of finding a function from its derivative is known as interation.

Given that dy/dx = 12x^2 + 4x - 5, find an expression for y.

y = 12((x^3)/3) + 4((x^2)/2) - 5((x^1)/1)

It would seem that

y=4x^3 + 2x^2 - 5x

but that is not quite the complete answer

Whenever you differentiate a constant you get zero,

e.g. y = 7 dy/dx = 0

and so the expression for y above could have any constant on the end and still satisfy dy/dx = 12x^2 + 4x - 5

The answer to this example is therefore

y= 4x^3 + 2x^2 - 5x + c, where c is a constant.

y = 12((x^3)/3) + 4((x^2)/2) - 5((x^1)/1)

It would seem that

y=4x^3 + 2x^2 - 5x

but that is not quite the complete answer

Whenever you differentiate a constant you get zero,

e.g. y = 7 dy/dx = 0

and so the expression for y above could have any constant on the end and still satisfy dy/dx = 12x^2 + 4x - 5

The answer to this example is therefore

y= 4x^3 + 2x^2 - 5x + c, where c is a constant.

by hotgirl69xxx
December 22, 2004